Development of a Microwave Instrumentation System for the Determination of Moisture Content in Oil Palm Fruits - Lee, Kim Yee (2008)
This thesis describes the development of a microwave instrument for moisture content determination of oil palm fruits. The developed PC-based Six Port Reflectometer provides a simple, fast and accurate solution to the more expensive and bulky Vector Network Analyzer for monitoring the ripeness of oil palm fruit at various stages based on the moisture content measurement. The Microwave Office software (MWO) was used to design and analyzed the Six Port Reflectometer. Various coaxial sensors were simulated using FEMLAB to study the reflection coefficient of the sensor corresponding to the moisture content and ripeness stage of oil palm fruit. The developed Six Port Reflectometer operating at 2 GHz consists of a stripline ring junction, three diode detectors and an Analog to Digital converter. Two types of coaxial sensors were selected for this work: the open ended coaxial and monopole sensors. A computer software was developed using Agilent Visual Environment Engineering (VEE) graphical programming for hardware control and implement all computation work. The performance of the developed Six Port Reflectometer in reflection coefficient measurement was tested. The empirical equations which relate the measured reflection coefficient and moisture content were found. The comparison of a batch of 200 fruit samples was done and it is found that the empirical equations is in the best agreement with the samples follow by finite element method (FEM) simulation and capacitance model. The monopole sensor phase shift measurement was found to be the best for moisture content measurement of oil palm fruits with 3.5% mean error. In bunch measurement, the apical region has the highest accuracy of moisture content measurement with 2.7% mean error followed by equatorial region, 3.0%, and basal region, 5.8%. For whole bunch moisture content measurement, the mean error was found to be 3.8%. The uncertainty of the developed Six Port Reflectometer system is calculated to be 5.5% for reflection coefficient measurement. This study shows that the Six Port Reflectometer is suitable for moisture content measurement of oil palm fruit and bunch. It is simple, fast, accurate, and a portable instrumentation system. It is suitable for early quality check of fruit and bunch ripeness.